POETICS OF THE IMPRESSIONISM IN THE SHORT STORY OF IVAN FRANKO «DRIADA» - Holod, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The paper studies the elements of the impressionism in the short story of Ivan Franko «Driada». It elucidetes genre, compositive and stylistic peculiarities of the work of art.